Colonoscopy: an inquiry into indications, findings and their correlation at a tertiary care hospital - M. N., Raghuveer; Shetty, Harshavardhan; K., Madhusudhan (International Surgery Journal, 2019)
Background: Though colonoscopy is widely performed, the statistical data regarding its indications, findings, and the diagnostic yield are not widely documented especially in developing countries. This study is an attempt to determine such data in a group of patients who underwent colonoscopy at our hospital. Methods: This was a hospital‑based retrospective study carried out at the Department of General Surgery, MMC&RI, Mysore. The subjects were a total of 286 patients who underwent colonoscopies in the year 2017. The relevant data from colonoscopy register were recorded and tabulated. Results: The major indications in our study group were bleeding per rectum (25%), unexplained diarrhoea or dysentery (16%), pain abdomen (15%) and suspected malignancy (13%). Other indications included suspected inflammatory bowel disease (IBD), subacute intestinal obstruction, anaemia, mass per abdomen and suspected irritable bowel syndrome (IBS). More than one third (35%) had normal colonoscopic studies. The most common pathology found was malignancy (24%) followed by the spectrum of proctocolitis (20%). The indications which produced high diagnostic yields included suspected carcinoma (97%), bleeding per rectum (82%) and suspected IBD (80%). Significant number of patients with per rectal bleeding was diagnosed with malignancy (21%). The indications which produced low yields included subacute intestinal obstruction (31%), anaemia (45%), non-specific pain abdomen (50%) and suspected irritable bowel syndrome (18%). Conclusions: Colonoscopy is highly rewarding among patients who are being evaluated for suspected malignancies, lower gastrointestinal bleeding and suspected IBD. As such, certain indications produce a higher diagnostic yield than others, suggesting that a stricter patient selection criterion may be employed for performing colonoscopy especially in resource poor settings.